Extracellular Ca2+ Acts as a Mediator of Communication from Neurons to Glia - Torres, Arnulfo (2012)
Defining the pathways through which neurons and astrocytes communicate may contribute to the elucidation of higher central nervous system functions. We investigated the possibility that decreases in extracellular calcium ion concentration ([Ca(2+)](e)) that occur during synaptic transmission might mediate signaling from neurons to glia. Using noninvasive photolysis of the photolabile Ca(2+) buffer diazo-2 {N-[2-[2-[2-[bis(carboxymethyl)amino]-5-(diazoacetyl)phenoxy]ethoxy]-4-methylphenyl]-N-(carboxymethyl)-, tetrapotassium salt} to reduce [Ca(2+)](e) or caged glutamate to simulate glutamatergic transmission, we found that a local decline in extracellular Ca(2+) triggered astrocytic adenosine triphosphate (ATP) release and astrocytic Ca(2+) signaling. In turn, activation of purinergic P2Y1 receptors on a subset of inhibitory interneurons initiated the generation of action potentials by these interneurons, thereby enhancing synaptic inhibition. Thus, astrocytic ATP release evoked by an activity-associated decrease in [Ca(2+)](e) may provide a negative feedback mechanism that potentiates inhibitory transmission in response to local hyperexcitability.